The Effect of Physical Work Environment and Work Motivation on The Performance of State Civil Apparatus Employees in The Field of Public Health and Health Resource Services Cimahi City Government Health Office - Yudha Pratama, Achmad; Lestari, Dian (International Journal of Management Science and Information Technology, 2026)
One of the key metrics used to assess how well public sector entities are serving the population is the State Civil Apparatus's performance. This study aims to investigate how State Civil Apparatus in the Public Health Sector and the Health Resources Services Division of the Cimahi City Government Health Office perform in relation to their physical work environment and motivation. This study employs an associative strategy in conjunction with a quantitative approach. There were 40 participants in the study, with two direct supervisors serving as performance variable assessors and 38 State Civil Apparatus respondents serving as independent variable respondents The sampling procedure employs the census method since every member of the population is used as a research participant. Using the aid of the SPSS software version 25, data were gathered via the distribution of questionnaires and examined using statistical descriptive analysis, multiple regression analysis, and determination coefficients. The research instrument is validated using validity, reliability, and classical assumption tests prior to testing of hypotheses. The study's outcomes show that both the physical work environment and work motivation possess a simultaneous influence on State Civil Apparatus performance, and that State Civil Apparatus performance is positively impacted by the physical work environment. Additionally, most crucial element in raising State Civil Apparatus performance is work motivation. The study's conclusions show that enhancing the physical work environment quality and motivation of employees may contribute to the enhancement of the State's Civil Equipment performance within the execution of public services.
Keywords: Physical Work Environment; Work Motivation; Employee Performance